1997
DOI: 10.1021/ma9608582
|View full text |Cite
|
Sign up to set email alerts
|

Structural Heterogeneity in Poly(methyl methacrylate) Glasses of Different Tacticity Studied by Thermally Stimulated Current Thermal Sampling Techniques

Abstract: The thermally stimulated current thermal sampling (TSC-TS) technique was used to study the cooperative glass transition like relaxations in different tacticity poly(methyl methacrylates) (PMMAs) including iso-and syndiotactic forms. We use the high sensitivity of the TSC-TS method to study these weak and sometimes overlapping relaxations at a frequency of about 10 -3 Hz where one can resolve cooperative relaxations well below the main glass transition (Tg), even if the species are a minor fraction of the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 39 publications
6
33
1
Order By: Relevance
“…In accordance to literature PMMA should have a glass transition around 105 8C. [47] The somewhat higher T g values we recorded for neat PMMA are most likely due to the rapid heating and cooling rates (30 8C min À1 ) that were used to record the thermograms. In contrast to class I materials, the class II materials have higher glass transitions than compared to the neat PMMA due to the crosslinks caused by the Pt1-G1-methacrylate chromophore.…”
Section: Thermal Analysissupporting
confidence: 90%
“…In accordance to literature PMMA should have a glass transition around 105 8C. [47] The somewhat higher T g values we recorded for neat PMMA are most likely due to the rapid heating and cooling rates (30 8C min À1 ) that were used to record the thermograms. In contrast to class I materials, the class II materials have higher glass transitions than compared to the neat PMMA due to the crosslinks caused by the Pt1-G1-methacrylate chromophore.…”
Section: Thermal Analysissupporting
confidence: 90%
“…It is seen that both stretched samples show the relatively lower activation energy. Sauer and Kim 27 suggested that the lower values of E a indicate that the polymer chains are more homogenous in terms of their structural regularity and/or composition. This seems to agree with our results in Fig 6 that the unstretched PET shows the highest E a and the stretched PET at 95°C shows the lowest value.…”
Section: Resultsmentioning
confidence: 99%
“…The PS-b-PMMA films were then annealed under a vacuum at 180°C for 24 h since the glass transition temperatures of the two polymer blocks are higher than 100°C ͑T g = 100°C for PS and T g = 105°C for PMMA͒. 18,19 After annealing, the samples were exposed to UV radiation for 90 min under vacuum to degrade the PMMA blocks. Degraded PMMA was selectively removed by sonication in glacial acetic acid for 1 min, followed by rinsing with DI water.…”
Section: Methodsmentioning
confidence: 99%